The impact of subject positioning on body composition assessments by air displacement plethysmography evaluated in a heterogeneous sample - Horhat, Raluca; Miclos-Balica, Monica; Muntean, Paul; Popa, Sandra; Sima, Irina; Glisici, Bogdan; Cîrja, Onisim; Neagu, Adrian; Neagu, Monica (PloS one, 2022)
This study sought to evaluate the impact of subject positioning on body composition assessments by air displacement plethysmography using the BOD POD®. Eighty-two adults (42 men and 40 women), aged 26.1 ± 8.4 y (mean ± standard deviation), body mass index = 23.6 ± 4.8 kg/m2, were assessed by repeated measurements in two different positions: relaxed (legs apart, back away from the rear) and compact (legs together, arms near the body, back touching the rear). We relied on Bland-Altman analysis to quantify the agreement between results recorded in the two positions. Using body surface charts, we tested the hypothesis that posture-induced variability stems from differences in exposed skin area. Switching from compact to relaxed position resulted in a bias of -197 mL for body volume, -1.53% for percent body fat, and 1.085 kg for fat-free mass. The body surface area in contact with air was larger in relaxed position by 3632 ± 522 cm2. When body volume was expressed in terms of the actual area of exposed skin in the compact position, the percent body fat bias became 0.08%, with a 95% confidence interval of (-0.14, 0.29)%. Subject posture is a source of significant variability in air displacement plethysmography. The disagreement between results obtained in different positions can be eliminated by adjusting the surface area artifact, suggesting that subject positioning in the BOD POD® should be controlled to avoid changes in the amount of air maintained under isothermal conditions by the body.